Analysis of the Effect of in-Late Angle and Lower Valve Position in the Semi Jet Type Water Pump Installation Against Water Debit - Heri Kustanto; Wiyono Wiyono; Lujeng Widodo; M. Azzis Purnomo Adji; Antoni Yohanes (Fakultas Teknik, 2023)
The problem that often occurs in people who use semi-jet water pumps is that when the installation of the water pump has been completed, it turns out that the water discharge cannot flow as expected and the electricity consumption is quite large. This research is expected to get optimal results, when installing the water pump installation, it is expected to get the largest water discharge by varying the valve location with the in-late angle, so that it will reduce the time to use the water pump. The experimental results with the linear regression method show that optimal conditions are achieved at variation 8 meaning to maximize the water discharge at the semi-jet water pump, namely the location of the valve above with an in-late angle of 450. The results of the comparison between the average value of water discharge for general use conditions are 29 .6 liters/minute with an average value of water discharge under optimal conditions of 34.8 liters/minute, indicating that the value of water discharge under optimal conditions can increase the water discharge by 5.2 liters/minute = (34.8 liters/minute – 29 ,6 liter/minute), so there is an increase of 8.0745 % = [5,2 / (34,8+29,6)] x 100%.